2022
DOI: 10.1155/2022/8075611
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Monitoring and Spatiotemporal Evolution of Mining Area with Unmanned Aerial Vehicle and D-InSAR Technology

Abstract: The extraction of underground mineral sources has a significant negative impact on the local environment, results in land surface subsidence. As far as subsidence monitoring technology is concerned, leveling is the most accurate. However, leveling can only obtain discrete point data but not the whole area information of the subsidence basin. In this study, Differential Interferometric Synthetic Aperture Radar (D-InSAR) combined with Unmanned Aerial Vehicle (UAV) technology is used to study the subsidence chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This computation is based on the coordinates of image points in the measurement images and employs the principle of least squares, while also incorporating a limited number of ground control points as constraints [31,32]. In this study, we used the ContextCapture software (version 4.4.10) [33] developed by Bentley to process the UAV-acquired photos. The data processing procedure mainly comprises data import, photo teaming, air triangulation solution, ground control point extraction, and coordinate system conversion, as depicted in Figure 5.…”
Section: Uav Oblique Photogrammetry Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…This computation is based on the coordinates of image points in the measurement images and employs the principle of least squares, while also incorporating a limited number of ground control points as constraints [31,32]. In this study, we used the ContextCapture software (version 4.4.10) [33] developed by Bentley to process the UAV-acquired photos. The data processing procedure mainly comprises data import, photo teaming, air triangulation solution, ground control point extraction, and coordinate system conversion, as depicted in Figure 5.…”
Section: Uav Oblique Photogrammetry Data Processingmentioning
confidence: 99%
“…Sci. 2023, 13, x FOR PEER REVIEW 7 of 16 4.4.10) [33] developed by Bentley to process the UAV-acquired photos. The data processing procedure mainly comprises data import, photo teaming, air triangulation solution, ground control point extraction, and coordinate system conversion, as depicted in Figure 5.…”
Section: Uav Oblique Photogrammetry Data Processingmentioning
confidence: 99%
“…They concluded that underground mining aligns with the directional surface deformation and exerts a persistent and continuous impact on surface deformation. Xu et al [26][27][28][29][30][31][32][33] utilized D-InSAR, GNSS, and UAV technology to monitor surface subsidence in gypsum mines while they analyzed the stability of mined-out areas and evaluated the subsidence risk within mining regions. The study by Wang HN et al [15,[34][35][36] discovered that Persistent Scatterer Interferometric Synthetic Aperture Radar (PS-InSAR) and Small Baseline Subset Interferometric Synthetic Aperture Radar (SBAS-InSAR) technologies exhibit distinct advantages over D-InSAR technology in terms of long time-series analysis, atmospheric loss correlation, and monitoring accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…InSAR measures the surface deformation along the line of sight (LOS), which restricts the understanding of the movement mechanisms of the mining goaf [18]. Efforts [19], [20] have been made to overcome this limitation, particularly the integration with relevant data, such as offset tracking data [21], [22], airborne data [23], [24], leveling data [25], GPS data [26], and other auxiliary data [27], [28]. Another widely used strategy is the probability integral method (PIM) [29], [30], which is based on the surface movement model, and is frequently combined with TS-InSAR for subsidence analysis in mining areas.…”
Section: Introductionmentioning
confidence: 99%